Generation Z's National Revitalization Strategy to Enhance National Resilience Amidst Global Transformation - Yuwana Andri Saputra; Nabil Hukama Zulhaiba (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Revitalizing nationalism among Generation Z is a crucial step in rekindling a sense of patriotism amidst rapid global change. The massive development of globalization has had a significant impact on the perspectives of the younger generation, who tend to be more open to global identities than to national ones. This situation demands efforts to strengthen nationalism so that Generation Z maintains an awareness of themselves as citizens who play an active and responsible role in their nation and state. Efforts to revitalize nationalism can be implemented through various strategies, such as strengthening character education, utilizing social media as an educational tool, and implementing activities that instill national values. Furthermore, strengthening nationalism is also relevant in facing global challenges, including climate change, poverty, and international conflict. With a strong sense of nationalism, Generation Z is expected to be able to maintain their national identity while contributing constructively to global dynamics.